Analisis Perhitungan dan Pelaporan Pajak Pertambahan Nilai pada PT XYZ - Widodo, Condro; Luthfiyanti, Destriyana (VISA: Journal of Vision and Ideas, 2024)
This study examines the calculation and reporting of Value Added Tax (VAT) at PT XYZ, a property management company that rents out vacant land, buildings, and other facilities. PT XYZ as a Taxable Entrepreneur has the obligation to collect, calculate, and report VAT in accordance with applicable tax regulations in Indonesia. This research uses a qualitative descriptive method, with data obtained through interviews, direct observation, and literature studies. Based on the research conducted, it is known that PT XYZ has carried out the correct VAT calculation based on the Taxable Basis of the nominal rent and applied a VAT rate of 11% in accordance with Law Number 7 of 2021. The reporting process is carried out periodically through the VAT Periodic Notification Letter by attaching all proof of transactions and tax invoices issued. This research also identifies that PT XYZ complies with VAT payment procedures and manages its administrative aspects well. Based on the research results, it can be concluded that PT XYZ has fulfilled its responsibility to carry out taxation in line with existing regulations, demonstrating commitment to tax compliance and transparency.